Citra Tubuh (Body Image) Remaja Perempuan - Amalia, Lia (Sunan Kalijaga State Islamic University & The Asia Foundation, 2007)
A socio,cultural component has long been blamed for the excessive concern with the appearance of women. Typically, the media is blamed for creating an impossible thin ideal as a model for women to emulate, and such images in magazines and on TV have been cast as the cause of widespread use of excessive dieting and eating disorders to achieve the